Viral Economies - Kyriakopoulos, Leandros (Homo Virtualis, 2020)
The article examines the Covid-19 pandemic by investigating the ways in which viruses are mapped out through the biosciences and recognized as threats in informational systems. Two examples are analyzed that, although seemingly unrelated, intersect the assemblages of biological and communicational networks. The first one concerns the speed at which a third of the world's population was quarantined. The second one involves the readiness of the material-technical infrastructure to support, and the political planning to transfer, a multitude of social and labour activities onto digital platforms. The adjective ‘viral’ highlights the metonymic ways in which digital media locate the different economies of gene formation, circulation and communication of subjects, transport of goods and political decision-making, and adapt them in favour of the technologic of the network. And what is suggested is to view the advent of Covid-19 within the cultural logic of new media in order to understand the horizon of an oncoming modernity.